Calculation of the Size of Biomimetics Robots According to Needs and Purpose of Use - Vu, Tam Van (International Journal of Online and Biomedical Engineering (iJOE), 2020)
- In the 4th industrial revolution era, more countries and companies tend to use specialized robots to replace workers. Especially in a hazardous and high risks working environment, robots that perform human tasks are also humanistic. It’s even the unique solution to ensure life safety. Currently, scientists are much interested in robots that look, act like animals; including biomimetic robot models have capable of flexible mobility and widely application potential. However, it’s difficult to calculate, design and manufacture dynamic robots. In this article, the author will present an overview of dynamic robots and propose new methods and calculation techniques to design and build biomimetic robots. The experimental results show that proposals have contributed to solve those difficulties and being practically applicable to make a biomimetic robot.